IDENTIFICATION AND QUANTIFICATION OF PHENOLIC COMPOUNDS FROM RED GRAPE POMACE - ADINA FRUM; CECILIA GEORGESCU; FELICIA G. GLIGOR; ECATERINA LENGYEL; DIANA I. STEGARUS; CARMEN M. DOBREA; OVIDIU TITA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The wine industry generates a great amount of waste every year, thus its valorization is of most importance. This study uses red, fermented pomace from Cabernet Sauvignon and Feteasca Neagra cultivars. The phenolic compounds were extracted using four different extractions and the content of total polyphenols was determined using a spectrophotometrical method. Several phenolic compounds were analyzed using an HPLC method. The Cabernet Sauvignon pomace had the highest content of total polyphenols and total phenolic compounds analyzed and of quercetin, rutin, ferulic acid and resveratrol, while the Feteasca Neagra pomace had the highest content of gallic acid, syringic acid, cinamic acid and (+) - catechin. The caffeic acid and the chlorogenic acid were not found in any of the analyzed pomaces. These pomaces could be used in the food industry as functional ingredients.